PLANKTON CALENDARS OF THE INSHORE WATERS AT MANDAPAM, WITH A NOTE ON THE PRODUCTIVITY OF THE AREA - Raghu Prasad, R. (Indian Journal of Fisheries, 2015)
Planktological investigations in various parts of the world have established that there are divergences in the pattern of annual distribution of plankton at the same station as well as between closely adjacent stations in the same general region at the same time. Despite these differences certain trends or nebulous patterns become apparent from prolonged observations. To differentiate the fortuitous from the truly repetitive changes data should necessarily cover a number of years and the observations should be spaced as closely as possible. These ideal conditions are, however, often difficult to achieve.